Rapid nitration of adipocyte phosphoenolpyruvate carboxykinase by leptin reduces glyceroneogenesis and induces fatty acid release. - Anne-Marie Jaubert (Public Library of Science (PLoS), 2012)
Fatty acid (FA) release from white adipose tissue (WAT) is the result of the balance between triglyceride breakdown and FA re-esterification. The latter relies on the induction of cytosolic phosphoenolpyruvate carboxykinase (PEPCK-C), the key enzyme for glyceroneogenesis. We previously demonstrated that long-term (18 h) leptin treatment of rat epididymal WAT explants reduced glyceroneogenesis through nitric oxide (NO)-induced decrease in PEPCK-C expression. We investigated the effect of a short-term leptin treatment (2 h) on PEPCK-C expression and glyceroneogenesis in relation to NO production. We demonstrate that in WAT explants, leptin-induced NO synthase III (NOS III) phosphorylation was associated with reduced PEPCK-C level and glyceroneogenesis, leading to FA release, while PEPCK-C gene expression remained unaffected. These effects were absent in WAT explants from leptin receptor-deficient Zucker rat. Immunoprecipitation and western blot experiments showed that the leptin-induced decrease in PEPCK-C level was correlated with an increase in PEPCK-C nitration. All these effects were abolished by the NOS inhibitor Nω-nitro-L-arginine methyl ester and mimicked by the NO donor S-nitroso-N-acetyl-DL penicillamine. We propose a mechanism in which leptin activates NOS III and induces NO that nitrates PEPCK-C to reduce its level and glyceroneogenesis, therefore limiting FA re-esterification in WAT.